2003
DOI: 10.1046/j.1461-0248.2003.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighbour‐regulated mortality: the influence of positive and negative density dependence on tree populations in species‐rich tropical forests

Abstract: Density-dependent mortality has long been posited as a possible mechanism for the regulation of tropical forest tree density. Despite numerous experimental and phenomenological investigations, the extent to which such mechanisms operate in tropical forests remains unresolved because the demographical signature of density dependence has rarely been found in extensive investigations of established trees. This study used an individual-based demographical approach to investigate the role of conspecific and heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
305
5
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(353 citation statements)
references
References 45 publications
35
305
5
5
Order By: Relevance
“…However, most other studies of seedling and sapling growth and survival in forests have similarly detected density-dependent effects at scales < 30 m (Curran and Webb 2000, Hubbell et al 2001, Peters 2003, Uriarte et al 2004b, Comita and Hubbell 2009). …”
Section: Accepted Ar Ticlementioning
confidence: 93%
“…However, most other studies of seedling and sapling growth and survival in forests have similarly detected density-dependent effects at scales < 30 m (Curran and Webb 2000, Hubbell et al 2001, Peters 2003, Uriarte et al 2004b, Comita and Hubbell 2009). …”
Section: Accepted Ar Ticlementioning
confidence: 93%
“…Most empirical research on NDD in tree species has focused on seeds [18] and seedlings [22], although several studies have also detected NDD for later life stages, including saplings [19,23] and adult trees [24]. Few studies have integrated effects of NDD across life stages [25,26], and no studies, to our knowledge, have directly quantified the effects of NDD across all tree life stages, from seeds to adults.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood processes can influence survival, recruitment, and growth of plant species positively through facilitation (Wills et al, 1997) or negatively by competition (Getzin et al, 2006;Gratzer and Rai, 2004), and indirectly by specialist herbivores and pathogens (Dobbertin et al, 2001;Gunton and Kunin, 2007;Hyatt et al, 2003;Janzen, 1970;Peters, 2003). These processes together to regulate species coexistence (Pacala, 1989;Peters, 2003;Volkov et al, 2005;Wills et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have demonstrated density dependence of varying extents in different species (e.g., He and Duncan, 2000;Hubbell and Foster, 1986;Kenkel, 1988;Peters, 2003;Wills and Condit, 1999;Wills et al, 1997). However, it is still unclear to what degree and spatial scale that density-dependent interactions among species may play a role in plant populations, especially in diverse, mixed tree communities (Gunton and Kunin, 2007;John et al, 2002).…”
Section: Introductionmentioning
confidence: 99%